MASUKNYA UNSUR-UNSUR PEMIKIRAN SPEKULATIF DALAM ISLAM: KAJIAN ATAS LOGIKA DAN METAFISIKA AL-FĀRĀBĪ - Irfan AN (CMES (Center of Middle Eastern Studies), 2014)
Al-Farabi considered as a philosopher basic foundation of Islamic philosophy. He is also known as the second teacher (al-mu'allim al-Thani) because of his dominantability in logic and reliable commentator of Aristotle‟s thought (a great commentator ofthe first teacher). Al-Farabi managed appropriately in explaining the logic of Aristotle to the Arabic-speaking nations without changing the meaning of philosophy because heconsiders logic as a universal grammar that its validity was spread throughout the humanrace. In field of metaphysics, Al-Farabi able to explain neo-Platonism systematically byfocusing on the discussion of sense, God and cosmology. Through these thoughts, alFarabiwants to strengthen the core of the teachings of Islam that is monotheism, so there is a unity between religion and philosophy.